2011
DOI: 10.1044/1092-4388(2010/10-0071)
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Suprasegmental Speech Features via Bimodal Stimulation: Cochlear Implant on One Ear and Hearing Aid on the Other

Abstract: This study found a significant bimodal advantage for perception of all suprasegmental features, most probably due to the better low-frequency acoustic hearing that is provided by the HA. Outcomes suggest that in cases of residual hearing in the contralateral ear to the implanted ear, HA use should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…Taken together, the findings of Spitzer et al (2009), Most et al (2011, Kong et al (2015), and the present study suggest that both harmonicity cues and the temporal envelope in the low-frequency region may contribute to bimodal benefit for speech recognition. When only glimpses of vocoder speech are available to the listener, the continuous signal in the LF ear (which arises from improved perception of the target speech at low frequencies) may contribute to speech perception (1) by transmitting additional segmental cues related to manner of articulation and/or F1 frequency that are absent or weakly represented in the vocoded signal, and (2) by facilitating speech segmentation, thereby enhancing identification of syllable and word boundaries.…”
Section: A Role Of Lf Continuity In Bimodal Benefitsupporting
confidence: 76%
See 2 more Smart Citations
“…Taken together, the findings of Spitzer et al (2009), Most et al (2011, Kong et al (2015), and the present study suggest that both harmonicity cues and the temporal envelope in the low-frequency region may contribute to bimodal benefit for speech recognition. When only glimpses of vocoder speech are available to the listener, the continuous signal in the LF ear (which arises from improved perception of the target speech at low frequencies) may contribute to speech perception (1) by transmitting additional segmental cues related to manner of articulation and/or F1 frequency that are absent or weakly represented in the vocoded signal, and (2) by facilitating speech segmentation, thereby enhancing identification of syllable and word boundaries.…”
Section: A Role Of Lf Continuity In Bimodal Benefitsupporting
confidence: 76%
“…Improved lexical segmentation and improved perception of prosodic cues have been demonstrated in previous studies of EAS benefit (e.g., Spitzer et al, 2009;Most et al, 2011). Spitzer et al (2009) investigated the possibility that lowfrequency fine-structure cues contribute to bimodal benefit by supporting lexical segmentation.…”
Section: A Role Of Lf Continuity In Bimodal Benefitmentioning
confidence: 84%
See 1 more Smart Citation
“…The present eye-tracking results showed that differentiating primary and secondary stress-initial words was significantly faster with simulated bimodal listening than with simulated CI listening. This finding is consistent with previous studies using pitch-related tasks, such as melody identification (e.g., Kong et al, 2005), lexical tone identification (e.g., Li et al, 2014), and question-statement discrimination (Most et al, 2011;Straatman et al, 2010), that showed improved performance with EAS listening compared to CI alone.…”
Section: Discussionsupporting
confidence: 92%
“…The consistent use of HAs by the CI recipients in our study is in line with the reported finding that lowfrequency information (up to 0.3 kHz) may significantly improve speech perception scores even when by itself it might not offer any speech understanding [9]. It should however be emphasized that when bilateral/bimodal (CI/HA) hearing rehabilitation is chosen, HA function should be routinely monitored, the HA should be refitted as required [10], and the actual bimodal benefit should be periodically evaluated by bimodal task-specific testing [8,[11][12][13].…”
Section: Discussionmentioning
confidence: 99%